Diffuse galactic Gamma-rays from star clusters. (27th August 2020) - Nath, Biman B; Eichler, David
ABSTRACT: We demonstrate that young star clusters have a γ-ray surface brightness comparable to that of the diffuse Galactic emission (DGE), and estimate that their sky coverage in the direction of the inner Galaxy exceeds unity. We therefore suggest that they comprise a significant fraction of the DGE.